2013
DOI: 10.3758/s13414-013-0495-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of visual and auditory representational momentum in spatial tasks

Abstract: Similarities have been observed in the localization of the final position of moving visual and moving auditory stimuli: Perceived endpoints that are judged to be farther in the direction of motion in both modalities likely reflect extrapolation of the trajectory, mediated by predictive mechanisms at higher cognitive levels. However, actual comparisons of the magnitudes of displacement between visual tasks and auditory tasks using the same experimental setup are rare. As such, the purpose of the present free-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
(75 reference statements)
3
18
2
Order By: Relevance
“…The lower range of RM size in our study is in line with the finding that action paradigms result in larger visual RM size than perceptual paradigms. 1 Results from stimuli moving toward the midline in the study by Schmiedchen et al 9 confirm the effect of target velocity found in this study. However, our results do not support the finding that stimuli moving toward the periphery resulted in an opposite effect of target velocity on RM size.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The lower range of RM size in our study is in line with the finding that action paradigms result in larger visual RM size than perceptual paradigms. 1 Results from stimuli moving toward the midline in the study by Schmiedchen et al 9 confirm the effect of target velocity found in this study. However, our results do not support the finding that stimuli moving toward the periphery resulted in an opposite effect of target velocity on RM size.…”
Section: Discussionsupporting
confidence: 80%
“…Also, the current study is the first to provide the full range of localization cues by using broadband noise stimuli. Besides the differences in response measurement paradigm described above, these factors influencing spatial information may be underlying the difference in findings compared to the studies by Getzmann et al 6 and Schmiedchen et al 9 The similarities between RM in the present study and visual RM suggests that our stimuli were adequate in engaging the RM mechanism at all velocities examined. Future studies are needed to clarify the effect of spatial information on auditory RM.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This is mostly achieved by using a pointing task, where participants are instructed to indicate the perceived position of a sound source (Shankweiler 1961;Seeber et al 2010;Kerber and Seeber 2012;Kühnle et al 2012;Schmiedchen et al 2012Schmiedchen et al , 2013Freigang et al 2014a) or by alignment of the participant's head and gaze to the direction of the sound source (Lewald et al 2000). Another paradigm used to measure the localisation accuracy is the absolute identification task (Abel et al 2000), where participants have to indicate the sound direction by choosing one of several indicated sound source positions in an nalternative forced-choice task.…”
Section: Measuring Auditory Space Processingmentioning
confidence: 99%